2019
DOI: 10.1111/nph.15843
|View full text |Cite
|
Sign up to set email alerts
|

Dark metabolism: a molecular insight into how the Antarctic sea‐ice diatom Fragilariopsis cylindrus survives long‐term darkness

Abstract: Summary Light underneath Antarctic sea‐ice is below detectable limits for up to 4 months of the year. The ability of Antarctic sea‐ice diatoms to survive this prolonged darkness relies on their metabolic capability. This study is the first to examine the proteome of a prominent sea‐ice diatom in response to extended darkness, focusing on the protein‐level mechanisms of dark survival. The Antarctic diatom Fragilariopsis cylindrus was grown u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 83 publications
(118 reference statements)
2
49
0
Order By: Relevance
“…Upon reduction of irradiance (HL -LL), Fv/ Fm increased and the concentration of chla declined, although this was not significant. It must be noted that the use of chla (Fo) as a measure of biomass is viewed with caution because ice-associated taxa can rapidly modulate their pigment composition in response to irradiance (Mock et al, 2017;Kennedy et al, 2019). Thus, the decrease in chla may be partially explained by the ability of diatoms to reduce the ratio of chla to carotenoid pigments in response to the narrowing of the light spectrum (Mundy et al, 2005;Massom and Stammerjohn, 2010;Campbell et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon reduction of irradiance (HL -LL), Fv/ Fm increased and the concentration of chla declined, although this was not significant. It must be noted that the use of chla (Fo) as a measure of biomass is viewed with caution because ice-associated taxa can rapidly modulate their pigment composition in response to irradiance (Mock et al, 2017;Kennedy et al, 2019). Thus, the decrease in chla may be partially explained by the ability of diatoms to reduce the ratio of chla to carotenoid pigments in response to the narrowing of the light spectrum (Mundy et al, 2005;Massom and Stammerjohn, 2010;Campbell et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanisms underlying efficient shade-adaptation can also limit the capacity for photosynthetic adjustment when sudden changes in irradiance occur (Raven, 2011;Raven and Beardall, 2011). The extreme variation of PAR in the sea-ice environment has forced many diatom species to evolve mechanisms that enable rapid adjustment of their photosynthetic apparatus to either increase photon capture in low light or minimize damage from excess irradiance (Mock et al, 2017;Kennedy et al, 2019). However, high interannual variability in irradiance (Turner et al, 2008) and the increased occurrence of extreme climatic events (Massom and Stammerjohn, 2010) in this region will influence both the timing and magnitude of light transmission and subsequently the development of ice-associated microbial communities (Deppeler and Davidson, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Another condition that induces flux through the EDP in P. tricornutum was mixotrophic growth with glucose in the light (Zheng et al 2013). Similarly, the Antarctic sea-ice diatom Fragilariopsis cylindrus showed increased expression of EDP genes in prolonged phases of darkness (Kennedy et al 2019). Both Cyanobacteria and plants were also shown to utilize the EDP, especially under mixotrophic conditions and in a light-dark-regime (Chen et al 2016).…”
Section: Functional Degeneracy In Glycolysis: the Entner-doudoroff Pamentioning
confidence: 99%
“…A field study showed that Arctic kelps can preserve their photosynthetic capability throughout the 4-month polar night reflected by the stable chlorophyll a fluorescence and pigment content (Scheschonk et al, 2019). Recently, the molecular acclimation processes of microalgae to long-term darkness have been examined using transcriptomics (Nymark et al, 2013;Mock et al, 2017;Mundt et al, 2019) and proteomics (Bai et al, 2016;Kennedy et al, 2019). However, the above studies were mainly focused on the molecular responses of diatoms.…”
Section: Introductionmentioning
confidence: 99%